The impact of social media influencers on online customer journey: Trustfulness as a moderating factor - Ajamieh, Lara Mohammed Abu; Abuhashesh, Mohammad; Eid, Mohammad Badi’ Al Haj; Badran, Rand; Joudeh, Jamal M. (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the influence of three key characteristics of social media influencers: interaction, expertise, and personality on the five online stages of the customer journey, with trustfulness serving as a moderating factor. A quantitative research methodology was employed, utilizing data collected from participants in Jordan and analyzed using descriptive analysis in SPSS, multiple regression, ANOVA tests, and AMOS software. The findings indicate that interaction, expertise, and personality significantly impact the customer journey, with trustfulness playing a positive moderating role. However, expertise does not influence the awareness stage of the journey, while personality exerts the highest effect overall. The study underscores the importance of social media influencers in shaping consumer behavior and highlights their strategic role in marketing efforts. Businesses should prioritize influencers with strong personalities and high trustworthiness to maximize their impact, recognizing that expertise alone may not be sufficient at the awareness stage. These insights contribute to a deeper understanding of influencer marketing and provide practical implications for marketers seeking to optimize engagement and consumer decision-making.